Development of Website-Based Interactive Learning Media Using Google Sites on Sound Wave Material - Septianti, Roja; Firdaus, Thoha (Islamic Journal of Integrated Science Education (IJISE), 2024)
One of the difficulties students have in learning physics is due to external problems from teachers who do not utilize learning media. This research aims to develop website-based interactive learning media using Google Sites for sound wave material. This research method is research and development (R&D) with a 4D development design, which consists of 4 stages: define, design, develop, and disseminate. The instrument used in this research was an expert validation sheet. From the assessment results from media expert validators, a score of 89.63% was obtained with very valid criteria, while from material expert validators, a score of 83% was obtained with very valid criteria. From these results, it can be concluded that this learning medium is suitable for use as an interactive learning medium in class XI sound wave material